A feasibility study for a clinical decision support system prompting HIV testing1. Issue 6 (21st December 2016) - Chadwick, DR; Hall, C; Rae, C; Rayment, Ml; Branch, M; Littlewood, J; Sullivan, A
Abstract : Objectives: Levels of undiagnosed HIV infection and late presentation remain high globally despite attempts to increase testing. The objective of this study was to evaluate a risk‐based prototype application to prompt HIV testing when patients undergo routine blood tests. Methods: Two computer physician order entry (CPOE) systems were modified using the application to prompt health care workers (HCWs) to add an HIV test when other tests selected suggested that the patient was at higher risk of HIV infection. The application was applied for a 3‐month period in two areas, in a large London hospital and in general practices in Teesside/North Yorkshire. At the end of the evaluation period, HCWs were interviewed to assess the usability and acceptability of the prompt. Numbers of HIV tests ordered in the general practice areas were also compared before and after the prompt's introduction. Results: The system was found to be both useable and generally acceptable to hospital doctors, general practitioners and nurse practitioners, with little evidence of prompt/alert fatigue. The issue of the prompt appearing late in the patient consultation did lead to some difficulties, particularly around discussion of the test and consent. In the general practices, around 1 in 10 prompts were accepted and there was a 6% increase in testing rates over the 3‐month study period ( P = 0.169). Conclusions: Using a CPOE‐based clinical decision support application to prompt HIV testing appears both feasible and acceptable to HCWs. Refining the application to provide more accurate risk stratification is likely to make it more effective.